AdipoRon Alleviates Free Fatty Acid-Induced Myocardial Cell Injury Via Suppressing Nlrp3 Inflammasome Activation - Zhang YZ (Dove Medical Press, 2019)
You-Zhi Zhang,1 Yu-Lin Zhang,1 Qi Huang,1 Cong Huang,1 Zhi-Long Jiang,1 Fei Cai,1 Jian-Fen Shen2 1School of Pharmacy, Hubei University of Science and Technology, Xianning, Hubei 437100, People’s Republic of China; 2Department of Central Laboratory, The First Affiliated Hospital of Jiaxing University, Jiaxing, Zhejiang 314001, People’s Republic of ChinaCorrespondence: Jian-Fen ShenDepartment of Central Laboratory, The First Affiliated Hospital of Jiaxing University, 1882 Zhonghuan South Road, Jiaxing, Zhejiang 314001, People’s Republic of ChinaTel +86 573 8251 9007Email shenjf2008@163.comBackground: Hypoadiponectinemia is a high risk factor for type 2 diabetes and cardiovascular disease. Although adiponectin is a protective molecule in cardiovascular diseases, it is hampered due to short plasma half-life and high cost of production. This study aimed to investigate whether AdipoRon, a small-molecule adiponectin receptor agonist, alleviated saturated free fatty acids such as palmitic acid (PA)-induced cardiomyocyte injury by suppressing Nlrp3 inflammasome activation.Methods: Cell viability was used with MTT assay. Cell apoptosis and mitochondria membrane potential were detected by flow cytometry. We also detected the ROS production and colocolization of inflammasome protein with fluorescence and immunofluorescence microscopic analysis, respectively. Then, IL-1β was detected by Elisa assay and other protein expression was analyzed by Western blot.Results: Our observations demonstrated PA dose-dependently promoted the cell injury, and such high lipotoxicity induced impairment of cardiomyocytes was significantly attenuated by AdipoRon treatment. Moreover, PA markedly activated the first phase of Nlrp3 inflammasome (NF-ƙb) signaling. Notably, the stimulation of PA enhanced ROS production as regulators of Nlrp3 inflammasome activation. In addition, treatment with PA increased the Nlrp3 inflammasome protein expression and complex formation, while AdipoRon abolished it. Lastly, the suppressive effect of AdipoRon to PA-induced cell injury and Nlrp3 inflammasome activation was significantly reversed by Nlrp3 siRNA and pan-caspase inhibitor (z-vad-fmk).Conclusion: Taken together, these data suggested that AdipoRon suppressed PA-induced myocardial cell injury by suppressing Nlrp3 inflammasome activation. Thus, AdipoRon might possess potent protective effect in lipotoxicity injury such as obesity leading to cardiac disease.Keywords: adiponectin, AdipoRon, PA, inflammasome, cardiomyocytes